2021
DOI: 10.1159/000513004
|View full text |Cite
|
Sign up to set email alerts
|

Technical Considerations in Awake Craniotomy with Cortical and Subcortical Motor Mapping in Preadolescents: Pushing the Envelope

Abstract: <b><i>Introduction:</i></b> Unlike adult gliomas, the utility of combined application of awake anesthesia and intraoperative neurophysiological monitoring (IONM) for maximal safe resection in eloquent region gliomas (ERG) has not been established for pediatric population while it remains unexplored in preadolescents (below 11 years old). <b><i>Case Presentation:</i></b> We report 2 cases of awake craniotomy with IONM in an 8 and 9 year old for safe maximal resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Intraoperative neurophysiologic mapping in children poses significant methodologic, interpretative and logistic challenges that overall stem from the immaturity of nervous system. [1][2][3][4][5][6][7] In epilepsy surgery, intraoperative electrocorticography (ECoG) is classically used to aid identifying the epileptogenic zone (EZ), i.e., the area of the cortex that is necessary to resect to achieve seizure freedom. 8 Historically, Penfield and Jasper 9 tried to identify the EZ using interictal discharges during ECoG.…”
Section: Epilepsy Surgerymentioning
confidence: 99%
“…Intraoperative neurophysiologic mapping in children poses significant methodologic, interpretative and logistic challenges that overall stem from the immaturity of nervous system. [1][2][3][4][5][6][7] In epilepsy surgery, intraoperative electrocorticography (ECoG) is classically used to aid identifying the epileptogenic zone (EZ), i.e., the area of the cortex that is necessary to resect to achieve seizure freedom. 8 Historically, Penfield and Jasper 9 tried to identify the EZ using interictal discharges during ECoG.…”
Section: Epilepsy Surgerymentioning
confidence: 99%
“…For pediatric procedures, growing series and technical notes have been recently reported ( Delion et al, 2015 ; Trevisi et al, 2016 ; Lohkamp et al, 2019 ; Alcaraz García-Tejedor et al, 2020 ; Lohkamp et al, 2020 ; Ratha et al, 2021 ; Herta et al, 2022 ). In the last available review, results of 18 studies concerning 50 patients who underwent awake surgeries for tumors, epilepsy, and functional diseases are reported.…”
Section: Neurosurgical Implicationsmentioning
confidence: 99%
“…This dogma remained undisputed until these days. In a recent review, it was observed that, unlike adults, awake surgery has yet to be accepted as the standard of care in pediatric patients, especially in the preadolescent groups [ 28 ]. Only 9 cases of children below the age of 11 years were reported in the last 65 years, 5 of those from a very recent series from Sick Kids in Toronto and, of the remaining four, two were procedures for deep brain stimulation [ 29 ].…”
Section: Brain Surgery (Fig 1 )mentioning
confidence: 99%
“…Only 9 cases of children below the age of 11 years were reported in the last 65 years, 5 of those from a very recent series from Sick Kids in Toronto and, of the remaining four, two were procedures for deep brain stimulation [ 29 ]. But also among adolescents (11–19 years), who are presumed to be psychologically and intellectually more matured, only 49 cases of awake craniotomies have been reported in the literature [ 28 ].…”
Section: Brain Surgery (Fig 1 )mentioning
confidence: 99%